Employment during the Pandemic Based on Regulation of the Minister of Manpower No. 21 of 2021 - Pratiti Alma Nurlita; Mahendra Akbar Rachmadani; Putri Monica; Rachma Nadya Pratama Putri; Saputri Setyo Nur Haryani; Aseka Malikus Zachwa (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the legal protection for workers affected by the Covid-19 outbreak. Article 88 letter a paragraph 1 UURI No. 11 of 2020 concerning Job Creation, states that